(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article describes the concept of lexical unit and its essence. The use of lexical units in lyrical texts and the pragmatic feaures they represent are theoretically described. Pragmatic features of lexical units in Usman Azim’s works are analyzed.